ChemInform Abstract: Palcernuine, the First [5/6/6/6]‐Cernuane‐Type Alkaloid from Palhinhaea cernua f. sikkimensis. Issue 42 (September 2016) - Tang, Yu; Xiong, Juan; Zou, Yike; Nay, Bastien; Wang, Li‐Jun; Hu, Jin‐Feng
Abstract: isolation and structure elucidation of palcernuine (I)